APPLICATION OF SPEED UP ROBUST FEATURES (SURF) AND FEATURES FROM ACCELERATED SEGMENT TEST (FAST) FOR INTRODUCTION OF PLACE - Mhd. Furqan; Rakhmat Kurniawan; Mey Hendra Putra Sirait (Sean Institute, 2020)
With the current technology that is starting to develop rapidly, it can match an image with another image. In recognizing an image, there needs to be a process that will be carried out in image matching, but current image matching is still comparing pixels between two images. To compare between images, the color and resolution and shape of the image pixels affect the recognition results in an image. Therefore, to deal with this problem, the algorithms that can be used in the work process of this program are the Speed ​​Up Robust Features (SURF) algorithm and Features from Accelerated Segment Test (FAST). FAST is a method for determining the angle that is in an image while the SURF algorithm can describe the features that exist in an image so that image matching no longer matches between pixels but based on the descriptors that have been generated and the matched results will be listed on the database, using the SURF algorithm , there is no need to worry about the resolution, color, and shape of the image to be matched. Tests that were carried out were still successful with a precision value of 0.9, which means that the value of successful matching is 9% and with a recall value of 100% and a value that has reached 100% means that the number of points is similar to the number of points that have been matched